PENGARUH PROGRAM KESELAMATAN KERJA TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT. MUSI BANYUASIN INDAH - Usailan Oemar; Rully Alamsyah; Rio Riansyah (Sekolah Tinggi Ilmu Ekonomi Rahmaniyah Sekayu, 2018)
This study aims to determine the effect of work safety programs on employee productivity at PT. Musi Banyuasin Indah. The method in this research is simple linear regression model. The population in this study all employees of PT Musi Banyuasin Indah which amounted to 578 people. The sample in this study amounted to 86 respondents taken using random sampling. The data studied is employee questionnaire data of PT Musi Banyuasin Indah. The results of this study can be seen that there is a significant influence between the safety program on employee work productivity PT. Musi Banyuasin Indah. The result of kofisien termination obtained by value of R square (R2) equal to 0,312 or 31,2%. This means the work safety program affecting work productivity by 31.2%, the remaining 68.8% influenced by other variables/factors not included/investigated in this study.